LEVELS OF MICRO-MEGAKARYOCYTE AND MORTALITY OF PATIENTS WITH MYELODYSPLASTIC SYNDROME - Vera Lady Marlina Sitorus; Zulfikar Lubis; Vinisia Setiadji; Herman Hariman (Indonesian Association of Clinical Pathologist and Medical laboratory, 2019)
Myelodysplastic syndrome (MDS) is dysplasia or incorrect growth of blood cells in bone marrow and some have a tendency to become malignant. One of the evidence of myelodysplasia is the finding of micro-megakaryocytes in the marrow. Micro-megakaryocyte is small megakaryocyte with size of < 40 µm and has hypo-granular cytoplasm, with mono- or bi-nuclei. The introduction of micro-megakaryocyte as an evidence of MDS is still new and not too many report about this, however logically micro-megakaryocyte may produce reduce number and poor quality platelet. Therefore, this study was designed to investigate whether micro-megakaryocyte may relate to the reduction of platelet number and further to the mortality of the patients. 30 patients were recruited but later 4 were excluded due to loss of follow up. The remaining 26 cases were investigated where 17 died and 9 alive. The mean ± SEM of micro-megakaryocyte of patients who died and still alive are 61,87±3,43 and 44,63±10,28% respectively (p<0,01). Platelet levels from who died and still alive are 44,23±13,36 and 86,67±39,76 (103/µL) p<0,01. This finding shows that the increased level of micro-megakaryocyte could be use as a good prognostic marker for MDS especially in relation to mortality due to bleeding.